-9x-9=-3x-63

Simple and best practice solution for -9x-9=-3x-63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x-9=-3x-63 equation:



-9x-9=-3x-63
We move all terms to the left:
-9x-9-(-3x-63)=0
We get rid of parentheses
-9x+3x+63-9=0
We add all the numbers together, and all the variables
-6x+54=0
We move all terms containing x to the left, all other terms to the right
-6x=-54
x=-54/-6
x=+9

See similar equations:

| -x-49=2(2x+3) | | x-28=5(4x+2) | | 4(3x-5)-1=-x+5 | | 5x+27=2(x+5)-10 | | 26=2(3x+4) | | 2x-7=2(2x-4)+5 | | -2x-173=124-11x | | 42=2(4x+5) | | 5x-34=2(5x+3) | | 16=4(2x-4) | | 13x–2(X-4)=8x+1 | | 3(5x-3)-1=-4x-29 | | -201-2x=10x+75 | | 3(x-4)-5=2x-26 | | (x-4)-5=2x-26 | | -14x-63=-9x+32 | | -95=6x | | 2x+19=49-3x | | 4=3h-h+2+10 | | 6x-88=13x+171 | | x=4/2x-4 | | 8x+29=−21+3x | | 16=7t-9 | | 24+24x=150+10x | | X(13-2x)=15 | | -25+2x=43+4x | | x+9=7x+9+6x | | 122y=4 | | 2u-5/3=-1/5u-4/5 | | 2x²5x18=0 | | -9x-24=18-7x | | -11x-90=165+6x |

Equations solver categories